MRI and the distribution of bone marrow fat in hip osteoarthritis. Issue 1 (2nd June 2016) - Gregory, Jennifer. S.; Barr, Rebecca J.; Varela, Victor; Ahearn, Trevor S.; Gardiner, Jennifer Lee; Gilbert, Fiona J.; Redpath, Thomas W.; Hutchison, James D.; Aspden, Richard M.
Abstract : Purpose: To characterize the distribution of bone marrow fat in hip osteoarthritis (OA) using magnetic resonance imaging (MRI) and to assess its use as a potential biomarker. Materials and Methods: In all, 67 subjects (39 female, 28 male) with either total hip replacement (THA) or different severities of radiographic OA, assessed by Kellgren–Lawrence grading (KLG), underwent 3T MRI of the pelvis using the IDEAL sequence to separate fat and water signals. Six regions of interest (ROIs) were identified within the proximal femur. Within each ROI the fractional‐fat distribution, represented by pixel intensities, was described by its mean, standard deviation, skewness, kurtosis, and entropy. Results: Hips were graded: 12 as severe symptomatic (THA), 33 had KLG0 or 1, 9 were KLG2, 11 with KLG3, and 2 with KLG4 were analyzed together. The fractional‐fat content in the whole proximal femur did not vary with severity in males (mean (SD) 91.2 (6.0)%) but reduced with severity in females from 89.1 (6.7)% (KLG0, 1), 91.5 (2.9)% (KLG2), 85.8 (16.7)% (KLG3, 4) to 77.5 (11.9)% (THA) (analysis of variance [ANOVA] P = 0.029). These differences were most pronounced in the femoral head, where mean values fell with OA severity in both sexes from 97.9% (2.5%) (KLG0, 1) to 73.0% (25.9%) (THA, P < 0.001) with the largest difference at the final stage. The standard deviation and the entropy of the distribution both increased ( P < 0.001). Conclusion: Descriptors of the fractional fat distribution varied little with the severity of OA until the most severe stage, when changes appeared mainly in the femoral head, and have, therefore, limited value as biomarkers. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:42–50.